E-WORKSHEET ORIENTED PROBLEM BASED LEARNING TO FOSTER SCIENTIFIC LITERACY: AN ANALYSIS OF PRESERVICE BIOLOGY TEACHERS’ COMPETENCE IN DEVELOPING LEARNING TOOLS - Ariska, Raja Novi; Rangkuty, Sailana Mira (Universitas Negeri Medan, 2025)
This study investigates the competencies of preservice biology teachers in developing e-worksheets based on Problem-Based Learning (PBL) to enhance students’ scientific literacy. Indonesian students’ consistently low performance in international assessments such as PISA highlights the need for innovative learning tools to improve instructional quality. PBL has been recognized as an effective approach to promoting scientific literacy, and preservice teachers must be equipped to design high quality materials for 21st century classrooms. A qualitative descriptive method was applied with 10 seventh-semester biology education students enrolled in a TPACK course at Samudra University. Participants were tasked with designing e-worksheets integrated with PBL principles. Data were collected through rubric-based document analysis, evaluating pedagogical competence in PBL integration, scientific literacy alignment, technological content knowledge (TCK), and overall product quality. Findings show that most participants effectively integrated PBL components (79.5%), aligned designs with scientific literacy goals (82.5%) and overall quality of e-worksheet (82%), though challenges remain in contextualizing problems and optimizing technological content knowledge (70%). Strengthening preservice teachers’ pedagogical and technological competencies is essential for preparing high-quality future educators.